Pengalaman Pembelajaran Guru MIS Mathlail Khoir Selama Masa Pandemi Covid-19 - Aan Noverizky; Yanti Hasbian Setiawati (Fakultas Syariah IAIN Laa Roiba Bogor, 2021)
This is article aims to find out what methods are taken by teacher in teaching children during the Covid Pandemic 19. The method used in the case study is trough interviews, by interviewing R1, R2, R3, R4, R5, and R6. The results show that the learning method taken is DARING ( Method in the Network ) through social media which is widely used whatsapp by sending material through Audio, Visual, and Audio Visual. In particular the assessment taken not only from the values of assignments given by the teacher board, even the assessment of character can also be seen its development. Such as when taking daily tests students are prohibited from cheating both with books and mobile phones. Indirectly the role of parents also helped the council of teachers to assist the course of learning during the covid pandemic 19. In general the role of parents who appear is as a guide, educator, guardian, developer, and supervisor. Cooperation is needed between the two parties so that there are no misunderstanding in distance learning during the covid pandemic 19. Keyword :